2016
DOI: 10.3109/0886022x.2016.1164064
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal circadian blood pressure regulation in children with nocturnal enuresis

Abstract: Subtle abnormalities of circadian BP regulation in enuretic children indicated by a selective elevation of nocturnal SBP, DBP, and MAP, and attenuated nocturnal dipping may reflect sympathetic hyper activation and its possible role in pathogenesis of enuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…They looked specifically at enuretic children with nocturnal polyuria, and found that they had more bodily movements – a sign of arousal – than their dry peers . Whether this finding can be extrapolated to other groups of enuretic children remains to be seen, but subjective indicators of poor sleep are accumulating, and recent studies showing higher nocturnal blood pressure in enuretic children than normal controls point in the same direction . In short, the sleep of enuretic children might be “deep” but “poor”.…”
Section: Sleep and Arousalmentioning
confidence: 99%
“…They looked specifically at enuretic children with nocturnal polyuria, and found that they had more bodily movements – a sign of arousal – than their dry peers . Whether this finding can be extrapolated to other groups of enuretic children remains to be seen, but subjective indicators of poor sleep are accumulating, and recent studies showing higher nocturnal blood pressure in enuretic children than normal controls point in the same direction . In short, the sleep of enuretic children might be “deep” but “poor”.…”
Section: Sleep and Arousalmentioning
confidence: 99%
“…Together with markers for oxidative stress, we found a 2.4-fold increase in adrenalin levels during wet nights and the presence of proteins relevant to blood pressure regulation. Kruse et al provided evidence of an increased nocturnal mean arterial pressure in NE children with polyuria and described a positive correlation between average nocturnal mean arterial pressure and nocturnal urine volume [ 38 ], findings that have been confirmed in other studies [ 39 ]. Further in line with this, we found increased levels of uromodulin (also in validation experiments) on wet nights compared to dry nights, which seems relevant since uromodulin is described to be important in sodium handling, blood pressure regulation, and modulation of oxidative stress in the body [ 40 ].…”
Section: Discussionmentioning
confidence: 77%
“…This lack of difference suggested the presence of white-coat hypertension in the control group. In their study, Yuce O et al (16) , evaluated 28 patients with monosymptomatic enuresis aged between 6-15 years based on 24-hour blood pressure measurements and found higher heart rates in enuretics which they thought to be probably related to increased arterial baroreceptor reflex responses. Normally, increased arterial pressure stimulates arterial baroreceptors in the aortic arch and carotid sinus area which leads to reflex inhibition of sympathetic efferent nerve activity and a decrease in heart rate with increased stimulation of parasympathetic efferent nerve activity.…”
Section: Discussionmentioning
confidence: 99%